2003 Kansas Performance Tests with Sunflower Hybrids - Evans, Patrick M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Sunflower performance tests were conducted by the Kansas Agricultural Experiment Station to provide farmers, extension workers, and private industry with unbiased agronomic information on many of the sunflower hybrids marketed in the state. Environmental factors affecting test results and cultural practices are presented for each individual test site.
Keywords: Kansas; Sunflower hybrids; Yield; Oil percentage; Statistical analysis; Seed size